Post-pandemic nutritional status of schoolchildren in an educational institution in Huánuco, Peru - Palacin-Fraga, Maruja (2024)
Objective. To demonstrate the effect of a Prenatal Educational Program on the knowledge of risk factors in pregnant women attended at a national hospital in Lima, Peru. Methods. A quasi-experimental study with control and experimental groups was designed, applying pre- and post-intervention measurements. The instrument used was a validated scale to assess knowledge of risk factors, applied to a sample of 20 pregnant women in each group. The chi-square test was used for hypothesis testing. Results. The results showed no signifcant difference in age, previous pregnancy, number of pregnancies, and socioeconomic level between the control and experimental groups (p > 0.05). Additionally, the Prenatal Educational Program had a positive effect on the knowledge of risk factors (p < 0.001). Conclusions. The relevance of implementing evidence-based educational programs on key variables in pregnancy can be determined.